'It's Not OK', but 'It' never happened: parental alienation accusations undermine children's safety in the New Zealand Family Court. Issue 1 (2nd January 2020) - Mackenzie, Deborah; Herbert, Ruth; Robertson, Neville
ABSTRACT: While the public campaign slogan in New Zealand when referring to family violence, is 'It's Not OK', many women in New Zealand report that the Family Court prefers the catchphrase 'It never happened'. When women and children escaping violence and abuse reach out to the New Zealand Family Court for protection believing the justice system will help them, they often enter an alternative reality where they are not believed and are subsequently made less safe. This is particularly so for those women whose well-founded fears for their children's safety get reinterpreted as evidence of a deliberate attempt to alienate the children from their fathers. The Backbone Collective, an independent organisation, surveyed New Zealand women about their experiences in the Family Court, finding that many women reported being accused of parental alienation. This paper investigates the sources of these allegations of parental alienation and how they impact mothers and their children. We argue that the use of parental alienation in the New Zealand Family Court is undermining the international rights of children.